2021
DOI: 10.1039/d1sc01661j
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and computational studies of the mechanism of iron-catalysed C–H activation/functionalisation with allyl electrophiles

Abstract: Experimental and computational studies support an inner-sphere radical pathway for iron-catalysed C–H activation/functionalisation with allyl electrophiles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 38 publications
1
11
0
Order By: Relevance
“…Hence, complex 9 , despite being an iron­(II) alkoxide similar to 6 , was found to be inert toward allene 2 , with no reaction observed according to an 1 H NMR spectroscopic analysis of an equimolar solution of 2 and 9 in C 6 D 6 . A similar effect has also recently been reported, where the use of strongly chelating diphosphine ligands leads to reduced reaction rates in iron-catalyzed C–H allylations . This striking difference between iron­(II) alkoxides 6 and 9 is attributed to the increased coordination strength of dmpe in the latter complex.…”
Section: Results and Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Hence, complex 9 , despite being an iron­(II) alkoxide similar to 6 , was found to be inert toward allene 2 , with no reaction observed according to an 1 H NMR spectroscopic analysis of an equimolar solution of 2 and 9 in C 6 D 6 . A similar effect has also recently been reported, where the use of strongly chelating diphosphine ligands leads to reduced reaction rates in iron-catalyzed C–H allylations . This striking difference between iron­(II) alkoxides 6 and 9 is attributed to the increased coordination strength of dmpe in the latter complex.…”
Section: Results and Discussionsupporting
confidence: 78%
“…Most mechanistic proposals on the mode of operation of iron-catalyzed C–H activation reactions are thus far supported by a limited amount of experimental data. Currently, only a few in-depth studies have been reported, namely on the arylation, alkylation, and allylation of aromatic amides with triazole ,, and quinoline directing groups and on the hydroarylation of allenes enabled by weak O -coordination (Scheme ). In the former studies, the mechanistic manifold proposed was supported by the isolation of iron­(II) cyclometallated species combined with Mößbauer spectroscopic studies and stoichiometric experiments (Scheme a). Subsequently, a low-valent Fe(0)/Fe­(II) manifold was proposed by Ackermann and co-workers for the [Fe­(PMe 3 ) 4 ]-catalyzed hydroarylation of allenes (Scheme b) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In consequence, computational data are often crucial in this field, and integrated closely with other experimental techniques. 77,78 When exploring double bond isomerization catalysis by an iron(II) β-diketiminate complex (Scheme 7 79 ), we found that we needed to bring a full spectrum of synthetic, computational and spectroscopic insights to bear to develop and assess a mechanistic proposal, as these catalysts can access different spin states along the reaction coordinate. With minimum energy crossing points (MECPs) difficult to determine, experimental data were at times easier to obtain than S C H E M E 5 Proposed mechanistic pathway for Suzuki-Miyaura cross-coupling by a dichloro-bis(aminophosphine) complex.…”
Section: Experimental Approaches Particularly Useful To Computational...mentioning
confidence: 99%
“…In this field, techniques such as Mössbauer, EPR, and related inorganic spectroscopic approaches can also contribute useful experimental insights, although we note that such equipment is less common in research laboratories than NMR, IR, and ESI‐MS while the interpretation of measurements is more involved, often requiring computational input. In consequence, computational data are often crucial in this field, and integrated closely with other experimental techniques 77,78 …”
Section: Experimental Approaches Particularly Useful To Computational...mentioning
confidence: 99%